V2 Data for Accelerated calibrationless parallel transmit mapping using joint transmit and receive low-rank tensor completion - Hess, A; Chiew, M (University of Oxford, 2021)
Data were created to test and evaluate an image reconstruction algorithm for accelerated parallel transmit mapping. The method is termed Transmit Low Rank (TxLR). It incudes images for transmit field mapping, both synthetic and measured.